1997
DOI: 10.1016/s0040-6090(97)00095-3
|View full text |Cite
|
Sign up to set email alerts
|

Oblique evaporation and surface diffusion

Abstract: The special structure of obliquely evaporated films has its origin in shadowing phenomena during film growth. Because of shadowing, the film consists of bundles of inclined columns with the bundles being aligned perpendicularly to the vapour incidence direction. The column inclination angle lies between the film normal and the vapour incidence direction. Different models found in literature relating process parameters and film structure are discussed. It is found that surface diffusion plays an important role,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
256
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(277 citation statements)
references
References 45 publications
12
256
0
Order By: Relevance
“…This is possible within a substrate-bias window, and depends on the growth conditions (target voltage and inclination angle of the substrate). For example, an increase in V T from 740 to 1000 V led to growth of bccTa at a lower V b value -a decrease from 70 V to 30 V. Many researchers have studied the growth of bcc-Ta on Si substrates [2][3][4][5][6][7][8][9] and have shown that stresses induced by ion bombardment can influence the structure of the deposited Ta film. The HIPIMS discharge is highly ionized and a large fraction of the ions bombarding the growing film consists of ions of the sputtered material [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is possible within a substrate-bias window, and depends on the growth conditions (target voltage and inclination angle of the substrate). For example, an increase in V T from 740 to 1000 V led to growth of bccTa at a lower V b value -a decrease from 70 V to 30 V. Many researchers have studied the growth of bcc-Ta on Si substrates [2][3][4][5][6][7][8][9] and have shown that stresses induced by ion bombardment can influence the structure of the deposited Ta film. The HIPIMS discharge is highly ionized and a large fraction of the ions bombarding the growing film consists of ions of the sputtered material [19].…”
Section: Discussionmentioning
confidence: 99%
“…The nucleation and growth conditions, i.e. the impurity levels [6] and the number of defects [7] also influence the phase formation. Face and Prober [4] and Window et al [8] used ion-beam sputtering, and showed that it is possible to obtain bcc-Ta by depositing a thin Nb layer prior to deposition of the Ta film.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements were carried out at four different directions of x (vapour incident direction) and y axes of the sample as well as two diagonal directions. These measurements provide us with the required data to evaluate the degree of anisotropy in the structure of the produced samples due to the structural differences (tilt angle, number of arms) and the bundling effect in these obliquely deposited thin films [25]. Resistivity of the films was calculated using [26]:…”
Section: Electrical Resistivitymentioning
confidence: 99%
“…The cross-section of the columns is generally elliptical. For crystalline materials, a specific texture is also observed, i.e., the orientation of the main axes of the crystal are dependent on the incidence angle and the deposition parameters [57].…”
Section: ) Layer Morphologymentioning
confidence: 99%